2008
DOI: 10.1007/s11103-008-9391-8
|View full text |Cite
|
Sign up to set email alerts
|

Rice DREB1B promoter shows distinct stress-specific responses, and the overexpression of cDNA in tobacco confers improved abiotic and biotic stress tolerance

Abstract: CBF/DREB (C-repeat binding factor/dehydration responsive element binding factor) family of transcription factors in plants is reported to be associated with regulation of gene expression under stress conditions. Here, we report the functional characterization of a DREB transcription factor, DREB1B gene from rice (Oryza sativa ssp. indica). The OsDREB1B gene was differentially regulated at the transcriptional level by osmotic stress, oxidative stress, salicylic acid, ABA, and cold. A 745 bp promoter region of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 55 publications
(88 reference statements)
2
73
1
1
Order By: Relevance
“…Arabidopsis TF DREB1 in IIIc controls the expression of many stress-inducible genes. OsDREB1A and OsDREB1B, DREB1 orthologs in rice, are induced by cold stress, and the overexpression of OsDREB1 increased tolerance to highsalt and freezing stresses (Ito et al, 2006;Gutha and Reddy, 2008). These rice transgenic plants also showed growth retardation under normal conditions, implicating rice AP2/ERF TFs in group IIIc function as repressors of GA biosynthesis, although we cannot ignore the possibility that group IIIc regulates BR biosynthesis or response (Ito et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Arabidopsis TF DREB1 in IIIc controls the expression of many stress-inducible genes. OsDREB1A and OsDREB1B, DREB1 orthologs in rice, are induced by cold stress, and the overexpression of OsDREB1 increased tolerance to highsalt and freezing stresses (Ito et al, 2006;Gutha and Reddy, 2008). These rice transgenic plants also showed growth retardation under normal conditions, implicating rice AP2/ERF TFs in group IIIc function as repressors of GA biosynthesis, although we cannot ignore the possibility that group IIIc regulates BR biosynthesis or response (Ito et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Chinnusamy et al (2003) reported that ICE1, which is a nuclear gene encoding a MYC-like bHLH protein, has a crucial role in regulating some CBF genes. The role of ICE1-CBF/DREB1 singling pathway in increasing cold tolerance has been investigated in different plant species such as A. thaliana (Welling & Palva 2008;Chen et al 2009;Fursova et al 2009;Yang et al 2011), Cucumis sativa , Triticum aestivum (Miller et al 2006;Morran et al 2011), Hordeum vulgare L. (Stockinger et al 2007;Campoli et al 2009), Solanum tuberosum (Behnam et al 2007), eucalyptus (Navarro et al 2009), Nicotiana plumbaginfolia (Gutha & Reddy 2008), apple (Artlip et al 2014), etc. Badawi et al (2008 reported that there are two ICE1 homologs, TaICE141 and TaICE187, in wheat and they up-regulate the expression of CBF group IV genes in wheat.…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…Many key genes have been identified that are involved in the regulatory networks under abiotic stress (Seki et al, 2007). Probably the best studied group of TFs involved in abiotic stress particularly, in drought and cold tolerance are the DREB1 genes (Gutha and Reddy, 2008;Oh et al, 2007;Qin et al, 2007;Sakuma et al, 2006). Many osmotic stress inducible genes contain a conserved drought responsive element (DRE) in their promoters (Shinozaki and Yamaguchi-Shinozaki, 2000;Thomashow, 1999).…”
Section: Engineering Stress Tolerance By Overexpressing Dreb Tfsmentioning
confidence: 99%